Comparative Effectiveness and Safety of Original Gabapentin and Generic Gabapentin in Treating Patients with Neuropathic Pain at Siriraj Hospital, Bangkok, Thailand - Chaisewikul, Rungsan; Saejong, Ratikorn; Tongsai, Sasima; Thamlikitkul, Visanu (Siriraj Medical Journal, 2020)
Background: Neuropathic pain (NP) develops as a consequence of a lesion or disease affecting the somatosensory system. Patients with severe NP usually suffer from pain and may need many treatment options. Drugs frequently prescribed for treatment of NP include amitriptyline, carbamazepine, gabapentin, and pregabalin. Objective: To compare the effectiveness and safety between original gabapentin (NeurontinÂ® ) and generic gabapentin (Gabapentin SandozÂ® ) in treating patients with NP at Siriraj Hospital. Methods: The study was a non-inferiority retrospective study. The medical records of the eligible patients who received gaba- pentin for NP were retrieved and all relevant data were extracted and recorded. Effectiveness and safety of both formulations of gabapentin were analyzed. Results: There were 356 NP patients who received original gabapentin and 356 NP patients who received generic gabapentin in which 105 patients received only generic gabapentin and 251 patients had received original gabapentin prior to receiving generic gabapentin. Demographic and underlying conditions of the patients leading to receiving gabapentin were not significantly different. Favorable clinical responses were observed in 91.0% (95% CI: 87.6, 93.6) and 95.2% (95% CI: 92.5, 97.0) of the patients who received original gabapentin and generic gabapentin, respectively. Effectiveness of generic gabapentin was not inferior to that of original gabapentin. Incidences of adverse events in the patients who received only original gabapentin and generic gabapentin were 29.2% (95% CI: 24.7, 34.1) and 28.6% (95% CI: 20.8, 37.9) respectively (p-value = 0.996). Conclusion: The effectiveness and safety of generic gabapentin and original gabapentinin for treatment of patients with NP at Siriraj Hospital were comparable.